Pembuktian sains dalam sunah - Zaghlul An_Najjar (Amzah, 2006)
ir, jil.1,c.1-3 ; jil.2,c.1-3/tr, jil.1=c.4; jil.2=c.4/ir,jil.1,c.5/ jil.1 =c.6-8, jil.2 =c.5-7, jil.3 =c.1-3/ws.jl.3.c.4-6/tr, jil.1=c.9; jil.2=c.8/oen, Jil.2=c.9;Jil.3=c.7